PENYELESAIAN PERKARA MELALUI PRODEO DI PENGADILAN AGAMA: UPAYA MEWUJUDKAN AKSES KEADILAN BAGI MASYARAKAT TIDAK MAMPU - Huda, Afiful; Adimas Pratama (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2025)
This article aims to analyze the case settlement mechanism through pro bono (prodeo) services in Religious Courts as one of the state's efforts to realize access to justice for underprivileged communities. Using a normative juridical method with a limited empirical approach, this study examines the legal basis, implementation, challenges, and strategies for strengthening the prodeo system. The findings indicate that although prodeo services are normatively well-regulated through Supreme Court regulations and related laws, their practical implementation still faces obstacles such as limited public awareness, complex administrative procedures, and budget constraints. Nevertheless, prodeo remains a concrete manifestation of the state's commitment to ensuring equality before the law and protecting human rights, particularly for the economically disadvantaged. Optimizing this service requires synergy between the judiciary, government, and legal aid institutions to ensure that substantive justice is truly accessible to all segments of society.